Effects of Supplements Differing in Fatty Acid Profile to Late Gestational Beef Cows on Steer Progeny Finishing Phase Growth Performance, Carcass Characteristics, and mRNA Expression of Myogenic and Adipogenic Genes - Shao, Taoqi (Animals (Basel), 2021)
SIMPLE SUMMARY: Maternal nutrition during late gestation affects fetal muscle and adipose tissue development, leading to persistent impacts on offspring postnatal growth and production performance. Fatty acids, especially essential fatty acids, play important roles in regulating protein and lipid metabolism. Therefore, the objective of the current study was to investigate the effects of maternal fatty acid supplementation during late gestation on beef cattle progeny finishing phase growth performance, carcass characteristics, and mRNA expression of genes involved in muscle and adipose tissue development. This study demonstrated that maternal supplementation with polyunsaturated fatty acids during late gestation increased the offspring’s feed ratio during the finishing phase. However, it had limited effects on finishing phase body weights, carcass characteristics, or relative mRNA expression in longissimus muscle and subcutaneous adipose tissue. Therefore, operations under similar systems could expect limited effects of maternal fatty acid supplementation on the growth and production performance of the finishing steers. ABSTRACT: The objective was to investigate the effects of feeding late gestational beef cows supplements differing in fatty acid profile on steer progeny finishing phase growth performance, carcass characteristics, and relative mRNA expression of myogenic and adipogenic genes. Seventy Angus-cross steers (initial body weight [BW] 273 ± 34 kg) born from dams supplemented with either 155 g DM/d EnerGII (CON, rich in palmitic and oleic acids) or 80 g DM/d Strata + 80 g DM/d Prequel (PUFA, rich in linoleic acid, eicosapentaenoic acid, and docosahexaenoic acid) for the last 77 ± 6 d prepartum were used. Longissimus muscle and subcutaneous adipose biopsies were collected to evaluate relative mRNA expression of genes related to myogenesis and adipogenesis. Steers were slaughtered at 423 ± 6 d of age. No treatment × time interaction or treatment effect (p ≥ 0.21) was detected for steer finishing phase BW, while steers from PUFA supplemented dams tended (p = 0.06) to have a greater gain to feed ratio (G:F). Neither carcass characteristics nor relative mRNA expression was different (p ≥ 0.11). In conclusion, late gestation PUFA supplementation tended to increase steer progeny finishing phase G:F, but had no effects on finishing phase BW, carcass characteristics, or relative mRNA expression during the finishing phase.